2007
DOI: 10.1021/jp0733825
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Interactions in Calix[4]arene−Perylene Bisimide Dye Conjugates:  Global and Target Analysis of Supramolecular Building Blocks

Abstract: The photophysical properties of two supramolecular building blocks oc and oc2 consisting of a perylene bisimide chromophore substituted with either one or two calix [4]arene units in the N-imide position as well as those of the reference compound oref without calix[4]arene substituents were investigated. A complete picture of the processes taking place after photoexcitation in toluene, CH 2 Cl 2 , and benzonitrile was obtained by means of UV/vis absorption, steady state and time-resolved emission, and femtosec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(109 citation statements)
references
References 57 publications
8
101
0
Order By: Relevance
“…These values are close to the electron transfer rate constant observed in calix [4]arene-PBI dyad (k CS intra = 4.0 × 10 10 s −1 in toluene; k CS intra is solvent-dependent). 62 To further confirm the intramolecular electron transfer in B-1, the fluorescence of B-1 in solvents with different polarities was studied ( Figure 4). The electron transfer induced fluorescence quenching will be more significant in polar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…These values are close to the electron transfer rate constant observed in calix [4]arene-PBI dyad (k CS intra = 4.0 × 10 10 s −1 in toluene; k CS intra is solvent-dependent). 62 To further confirm the intramolecular electron transfer in B-1, the fluorescence of B-1 in solvents with different polarities was studied ( Figure 4). The electron transfer induced fluorescence quenching will be more significant in polar solvents.…”
Section: Resultsmentioning
confidence: 99%
“…S1). 39,40 The aggregate form 65 of PBI 4 in MCH solvent also reveals slightly red-shifted absorption spectra as compared with that of PBI 1. Thus, we expect that PBI 4 is supposed to act as an exciton quencher in the self-assembled hetero-PBI aggregates composed of PBI 1 and PBI 4 (vide infra).…”
Section: Steady-state Absorption and Fluorescence Measurementsmentioning
confidence: 97%
“…Thus, it has been shown that already modestly electron-rich aromatic substituents such as alkylated and in particular alkoxylated phenyl groups quench the fluorescence in solvents of intermediate or high polarity by photoinduced electron transfer from the substituent to the electron-poor PBI scaffold. 33,34 In contrast to the imide substituents, substituents at core positions have a pronounced influence on the redox potentials and absorption properties of these dyes ( Figure 3). This opened the possibility to tune the dyes' functional properties while maintaining the self-assembly properties encoded at the imide subunits.…”
Section: Core-substituted Perylene Bisimidesmentioning
confidence: 99%